Pengaruh Faktor Keuangan dalam Profitabilitas Terhadap Harga Saham Perbankan Digital 2021 – 2023 - Maharani, Devania Keysha (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the influence of financial factors on profitability, namely Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (OEOI), with regard to the stock prices of digital banking and digitally transformed banking in Indonesia from 2021 to 2023. Methodology/approach: Quantitative research approach was used. The type of data used in this study is secondary data, with a population consisting of 12 digital banks and banking companies that have digital transformation listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Results/findings: The results of the study show that ROA and BOPO has a negative and statistically significant effect on stock prices, ROE and NIM has a positive and statistically significant effect on stock prices. Conclusions: COVID-19 has accelerated digital banking and shifted investor focus to tech innovation. ROA and OEOI had negative effects on stock prices (H1 and H4 rejected), while ROE and NIM had positive effects (H2 and H3 accepted). Limitations: This research is limited to the financial performance ratios used, and the results focus on digital banking companies in Indonesia only. Contribution: This study can be used as a literature reference for further research, especially on the influence of financial factors in terms of profitability on the share prices of digital banking in Indonesia.